Communication between general practitioners and consultants: what should their letters contain?. Issue 6830 (28th March 1992) - Newton, J.; Eccles, M.; Hutchinson, A.
Abstract : OBJECTIVE--To canvass the views of all general practitioners and consultants working in Newcastle upon Tyne on the content of referral letters and replies, the feasibility of standardising certain aspects of referral letters, and the use of communications data for audit purposes. DESIGN--A postal questionnaire was sent to all general practitioners and consultants in Newcastle upon Tyne in May 1991. Questions were asked about the clinical and administrative content of letters, the utility of standard categories to state the reason for referral, the idea of using letters for feedback purposes, and communications as a potential topic for professionally led audit. SETTING--Area served by Newcastle upon Tyne Family Health Services Authority and District Health Authority. RESULTS--Replies were received from 274 (77%) doctors (115 general practitioners and 159 consultants). A majority (225; 82%) were in favour of items defined as "always important" forming a minimum requirement for referral letters and for consultants' replies. Using standardised categories to state the reason for referral was not endorsed: 102 (89%) general practitioners and 132 (83%) consultants preferred referrers to use their own words. Using referral communications to provide feedback was less popular with consultants (54; 34%) than general practitioners (72; 63%). Finally, a majority of doctors (179; 65%) were in favour of using written communications as a topic for professionally led audit. CONCLUSIONS--A high degree of consensus exists among clinicians about the content of referral communications. Although doctors may still reject the concept of standardised communications, they have unambiguously endorsed a standard for communication that they can aspire to, and they are prepared to use it as a yardstick for their actual performance.